2015
DOI: 10.1007/s11356-015-4543-2
|View full text |Cite
|
Sign up to set email alerts
|

Photochemical degradation of PAHs in estuarine surface water: effects of DOM, salinity, and suspended particulate matter

Abstract: The photodegradation of several polycyclic aromatic hydrocarbons (PAHs) including phenanthrene, benzo(a)pyrene, and benzo(e)pyrene was studied under different estuarine conditions to elucidate the effects of dissolved organic matter (DOM), salinity, and suspended particles on PAH photodegradation in the estuarine surface water. Besides the competitive light absorption effect, DOM can accelerate the photodegradation of small PAHs such as phenanthrene by enhancing the formation of reactive intermediates and inhi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
23
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 42 publications
(24 citation statements)
references
References 47 publications
1
23
0
Order By: Relevance
“…These results support the conclusion that LWM PAHs (such as 3-ring PAHs) can be biodegraded more rapidly than HMW PAHs (such as 6-ring PAHs) [46,47], as the LWM PAHs degradation by-product, HCO 3 − , was probably increased [30]. It was reported that high salinity can accelerate the photodegradation of PAHs [48], but chloride as the representative ion of salinity, had a positive correlation with 2-ring PAHs and 3-ring PAHs (R 2 = 0.52 and R 2 = 0.82) in October 2014 for surface water, that might only manifest their coexistent sources. NO 3 was negatively correlated with LMW PAHs during 2014 in surface water, which suggested LMW PAHs removal accompanied by nitrification.…”
Section: Physio-chemical Indices Associated With Pahs Concentrationsupporting
confidence: 86%
“…These results support the conclusion that LWM PAHs (such as 3-ring PAHs) can be biodegraded more rapidly than HMW PAHs (such as 6-ring PAHs) [46,47], as the LWM PAHs degradation by-product, HCO 3 − , was probably increased [30]. It was reported that high salinity can accelerate the photodegradation of PAHs [48], but chloride as the representative ion of salinity, had a positive correlation with 2-ring PAHs and 3-ring PAHs (R 2 = 0.52 and R 2 = 0.82) in October 2014 for surface water, that might only manifest their coexistent sources. NO 3 was negatively correlated with LMW PAHs during 2014 in surface water, which suggested LMW PAHs removal accompanied by nitrification.…”
Section: Physio-chemical Indices Associated With Pahs Concentrationsupporting
confidence: 86%
“…Particulate-bound hydrocarbons may be thus deposited to sediment through vertical sinking (Dachs et al 2002;Duran and Cravo-Laureau 2016), transferred from sediment to water column via sediment resuspension events (Eggleton and Thomas 2004;Ko et al 2003), transferred to dissolved water phase from desorption processes (Baker et al 1991), may undergo photodegradation and biodegradation (Dachs et al 1999;Shang et al 2015) or may enter marine food web through ingestion of particles by filter feeders (Akkanen et al 2012). Overall, the fate and dynamics of hydrocarbons in the water column are largely driven by their partitioning between the particulate and dissolved phases, which is quantified via the particulate-water or particulate organic carbon (POC)-water partition coefficients (K d and K oc , respectively) (Herbes 1977).…”
Section: Introductionmentioning
confidence: 99%
“…The removal efficiencies were 51.6%, 86.6%, 92.0%, and 91.8% for CK 1 , CK 2 , T 1 , and T 2 , respectively. The removal of PHE in the control treatment showed that the abiotic loss of PHE (mainly through photodegradation and volatilization) (Luo et al, 2014;Shang et al, 2015) could beyond 50%. The removal efficiency of PHE in the U. prolifera treatment was much higher than that in the control treatment, indicating that U. prolifera was engaged in the removal of PHE.…”
Section: Resultsmentioning
confidence: 99%